Analisis Jabatan Dalam Peningkatan Kinerja Guru Di Sekolah - Ainun Ma’rifah; Mufti Hamidi; Siti Khotijah; Mu’alimin Mu’alimin (Jurnal Budi Pekerti Agama Islam, 2024)
Job analysis is one approach that can be used to improve teacher performance. Improving teacher performance is currently one of the main focuses in achieving optimal quality of education. Teachers are a key component in the learning process, and the quality of their performance has a significant impact on student learning outcomes. The aim of this research is to explain job analysis in improving teacher performance in schools by using literature review studies as a method of collecting data, analyzing, reading and taking notes as well as processing research materials. Data collection techniques involve collecting information from written or printed sources, such as books, journals, articles, reports and other documents by assessing procedures from the results of similar research that has been carried out by other people. The results of this research conclude that in job analysis, teachers must be placed in positions that are in accordance with their qualifications and skills. This allows teachers to use their abilities effectively and improve their performance. In addition, job analysis also helps in identifying the training and development needs of teachers, so that they can improve the quality of education provided.